Pembangunan dan Ekonomi Politik Turisme Massal di Daerah Istimewa Yogyakarta - Anggalih Bayu Muh Kamim (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2023)
This research aimed to explore the transition from community-based tourism into mass tourism which has been initiated by the government. Data was collected through in depth interviews, observation, and secondary data analysis. This research found that the central government has been creating mass tourism since the ‘80s, because the state was interested in making tourism become one of the main incomes after the end of oil boom era. Mass tourism was booming until the end of the ‘90s. Nevertheless, the decrease in international tourist arrival was occurred because of forest fires, economic crises, Bali Bombing I and II, and SARS pandemic. Unfortunately, Yogyakarta’s earthquake in 2006 has hindered the recovery process. One decade after the earthquake, a mass tourism was booming again which was marked by the expansion of hotel construction. There were negative impacts such as lack of water access for public, repression of the labour movement, and policies that neglected public participation. The government continued to develop mass tourism through RPJMD DIY 2017-2022 as the nexus of central and local government interests. Projects from RPJMD DIY 2017-2022 were done by cultures and repressions mobilization, thus lead to another problems such as worsened public interests marginalization, land and labour privatization.